2003
DOI: 10.7589/0090-3558-39.4.887
|View full text |Cite
|
Sign up to set email alerts
|

Health Evaluation of Pampas Deer (Ozotoceros bezoarticus celer) at Campos del Tuyú Wildlife Reserve, Argentina

Abstract: ABSTRACT:Samples from 14 free-ranging pampas deer (Ozotoceros bezoarticus celer) were collected in 1995 and 1998, at Campos del Tuyú Wildlife Reserve, Buenos Aires, Argentina. Hematology, serum chemistries, minerals and metals, and fecal parasites were analyzed. In addition, fecal ova and parasites were evaluated seasonally during 1998-2000. Serology for infectious diseases included bluetongue, brucellosis, bovine respiratory syncytial virus infection, bovine viral diarrhea/mucosal disease, infectious bovine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
2
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 11 publications
0
22
2
9
Order By: Relevance
“…High rates of PIV infection among these populations support incomplete immunization with infections and high rates of reinfection throughout life (9). Serologic studies have demonstrated common PIV exposure among wild hooved species in Alaska (67%) (28), the central Italian Alps (17%) (29), Argentina (43%) (30), Alberta (49%) (31), South Africa (25%) (32), and Quebec (82%-84%) (33).…”
Section: Discussionmentioning
confidence: 99%
“…High rates of PIV infection among these populations support incomplete immunization with infections and high rates of reinfection throughout life (9). Serologic studies have demonstrated common PIV exposure among wild hooved species in Alaska (67%) (28), the central Italian Alps (17%) (29), Argentina (43%) (30), Alberta (49%) (31), South Africa (25%) (32), and Quebec (82%-84%) (33).…”
Section: Discussionmentioning
confidence: 99%
“…Esses resultados são similares aos de GIRIO et al (2004) obtidos em amostras de veados-campeiros em estado feral da região de Nhecolândia, MS, e diferem dos encontrados, nos estados de Goiás e Mato Grosso do Sul, por MATHIAS et al (1999), título máximo de 400, e por UHART et al (2003) em amostras de veadoscampeiros de vida livre oriundas, respectivamente, dos estados de Goiás e Mato Grosso do Sul e da região dos Campos del Tuyú na Argentina, entre os anos de 1995 e 1998. Esses títulos sorológicos podem ser interpretados como uma infecção passageira ou uma imunidade de memória ou ainda um estágio inicial da leptospirose (FAINE, 1999).…”
Section: Discussaounclassified
“…Studies on wild animals often use manual methods with the hemocytomer (Almosny and Santos, 2001). Other examples of RBC counts for different species include Chital deer (Chapple et al, 1991), Brown mink (Weiss et al, 1994), Coatis (Silva et al, 1999), Pampas deer (Uhart et al, 2003), Pallas' cats (Brown et al, 2005), Capybaras (Madella et al, 2006) (Inoue et al, 2012), Moose (Rostal et al, 2012), Norwegian reindeer (Miller et al, 2013), Giant anteaters (Sanches et al, 2013) Black howler monkey (Santos et al, 2013). It is also possible to find studies on humans and domestic animals, that use the hemocitometer, e.g.…”
Section: Methodsmentioning
confidence: 99%
“…All RBC counting were conducted in less than 24h after sampling time (Brown et al, 2005;Sanches et al, 2013;Weiss et al, 1994).…”
Section: Methodsmentioning
confidence: 99%